A study on the awareness of biomimicry among students and practitioners around Klang Valley / Muhamad Zharin Hariz Mat Mazelan ... [et al.] - Mat Mazelan, Muhamad Zharin Hariz; Samsudin, Mohd Rashidy; Mohd Noor, Nur Dalilah; Ahmad Sabri, Nurul Ain; Mohd Nasir, Roziani; Mohd Nasir, Mohd Rozman; Ab Rahman, Mohamad Faizal; Mohd Roslam, Mohd Zulhilmi (Universiti Teknologi MARA, 2021)
The purpose of this study is to introduce the biomimicry design approach in educating future designers. The objectives are to define biomimicry design, to discover the characteristics of nature that influences biomimicry design and to develop the criteria and design consideration of Biomimicry influenced design. This process is meant to remind designers of the benefits nature has to offer in helping to solve many of the problems that society is currently grappling with today. In order to determine the understanding of biomimicry, the direct method have been implemented in terms of the biomimetic design process; applying the six stages: (1) Defining, (2) Analyzing, (3) Observing, (4) Selecting, (5) Implementing, and (6) Evaluating. Overall, this thesis is meant to encourage designers to think differently, forcing them to innovate, experiment, push and adapt their designs further than ever before. The objective at hand is to create good design that has also the potential to benefit mankind, the world and everything that encompasses it.